Practical Considerations for Translating Mesenchymal Stromal Cell-Derived Extracellular Vesicles from Bench to Bed - Pauline Po Yee Lui; Yung Tim Leung (MDPI AG, 2022)
Extracellular vesicles (EVs) derived from mesenchymal stromal cells (MSCs) have shown potential for the treatment of tendon and ligament injuries. This approach can eliminate the need to transplant live cells to the human body, thereby reducing issues related to the maintenance of cell viability and stability and potential erroneous differentiation of transplanted cells to bone or tumor. Despite these advantages, there are practical issues that need to be considered for successful clinical application of MSC-EV-based products in the treatment of tendon and ligament injuries. This review aims to discuss the general and tissue-specific considerations for manufacturing MSC-EVs for clinical translation. Specifically, we will discuss Good Manufacturing Practice (GMP)-compliant manufacturing and quality control (parent cell source, culture conditions, concentration method, quantity, identity, purity and impurities, sterility, potency, reproducibility, storage and formulation), as well as safety and efficacy issues. Special considerations for applying MSC-EVs, such as their compatibility with arthroscopy for the treatment of tendon and ligament injuries, are also highlighted.